PENERAPAN METODE STORYTELLING INTERAKTIF UNTUK MENINGKATKAN MINAT BACA MURID PADA TEKS NARASI DI KELAS IV SD NEGERI 071030 AFIA - Dian Juliarti Tanjung; Mastawati Ndruru; Adieli Laoli; Lestari Waruwu (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2026)
This study was motivated by the low reading interest of fourth-grade students in narrative texts at SD Negeri 071030 Afia. This condition was reflected in the students’ lack of interest, attention, and active involvement in reading activities. In addition, the learning process tended to rely on conventional teaching methods, which limited opportunities for students to participate actively in the learning process. This study aimed to improve students’ reading interest in narrative texts through the implementation of an interactive storytelling method. The study employed Classroom Action Research (CAR), which was conducted in two cycles. Each cycle consisted of four stages: planning, action implementation, observation, and reflection. The subjects of this study were 36 fourth-grade students of SD Negeri 071030 Afia. Data were collected through observation, questionnaires, and documentation. The collected data were analyzed both quantitatively and qualitatively to determine improvements in students’ reading interest and learning activities during the learning process. The results showed that the implementation of the interactive storytelling method was able to improve students’ reading interest in narrative texts. The percentage of students’ reading interest increased from 76.16% in Cycle I, categorized as high, to 85.98% in Cycle II, categorized as very high, representing an increase of 9.82%. Furthermore, students’ learning activities increased from 70.72% in Cycle I to 86.67% in Cycle II. Therefore, the interactive storytelling method was effective in improving students’ reading interest and active engagement in narrative text learning.